STUDI TENTANG APLIKASI KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) PADA BIDANG STUDI MATEMATIKA SMK NEGERI 1 GUNUNGSITOLI BARAT TAHUN PELAJARAN 2011/2012 - Harefa, Amin Otoni (DIDAKTIK, 2012)
abstract. The purpose of the study : 1). To find educational applications Unit Level Curriculum(SBC) in mathematics Â 2). To determine the constraints encountered in the application of the Education Unit Level Curriculum (SBC) specifically mathematics . This research was conducted at SMK Negeri 1 Gunungsitoli Baratin 2011/2012 . Subjects were Principal , Subject Teacher , Student and School Committee . The research method is qualitative research . Key instruments : research and survey instrumentation tape recorder , sheet interviews , open questionnaires , observation sheets . The findings of the study : 1). Application of SBC mathematics does not meet the standards set by the government , 2). the constraints faced; a.Gedung schools that are not yet available ; b.Ketersediaan learning resources are very less ; c.Fasilitas and supporting infrastructure of education is very less ; d.Intake of students is very less ; e.Minat and student motivation is low ; f.Partisipasi community in supporting education is lacking .Â Key Words: Aplication, KTSP, Mathematics, SMK